The Impact of the Pandemic Crisis on the National Economy - Daniela NECHITA (Dunarea de Jos University of Galati, 2021)
The pandemic crisis has destabilized the entire national economy, affecting, at the same time, businesses in all fields of activity, regardless of their size and economic strength. This crisis has divided the actors of the Romanian business environment into winners and survivors, even if many of the companies have definitively given up the idea of running a business. The effects of this crisis will be felt for a long time, so in order to remain on the market most businesses will have to reinvent themselves to withstand an extremely dynamic and uncertain economic and social environment.